O papel do capital social e das instituições no processo de construção da confiança interorganizacional - Mello, Cristiane Marques de (2014)
This study aimed to analyze and understand the role of social capital and institutions in the process of building interorganizational trust. In the present study, we adopted the concept of trust based on Bachmann and Inkpen (2011) institutions. Trust, this perspective is understood as a form of personal or collective action that is constitutively immersed in the institutional environment in which a relationship is laid, based on favorable assumptions about trust in future behaviors . The aim is to prove that trust is not only psychologically, but also in the social sphere, especially in institutions, which are evidenced by norms, beliefs, values which are socially legitimated. Our aim is to understand the social construction of trust in interorganizational relationships based on understanding of institutions and social capital, in three stages: the period before the building of trust (T-1) , during which the relationship confidence is being built (T ) and period in which the trust exists and new interactions are built (T+1). This research is characterized as qualitative and included the use of interviews. The sample consisted of 28 companies, owners, managers, directors and/or responsible for the furniture sector organizations in the towns of Linhares in Esprito Santo state and Arapongas in Paraná. For preparation and data analysis, we used the software NVivo 10, and then the techniques of narrative and content analysis. From the results, we found that social capital operates in all stages of the process, either as antecedent for relations, and sometimes as a facilitator for building and maintaining trust among companies. When trust between the parties is consolidated, the social capital of the organization loses strength on the history of the relationship. In this phase, the history of the relationship and trust in the actor are larger than the expectation based institutions.